Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/02699052.2016.1255777
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of disability and quality-of-life in non-geriatric and geriatric survivors after severe traumatic brain injury

Abstract: Disability decreased and HRQoL improved after TBI between 3-12 months. In geriatric patients this improvement was relevant for HRQoL only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…While the GOSE is the most widely used measure of global functional outcome following TBI and has been recommended as the standard outcome measure for TBI studies, it has not been validated in the elderly population. One group showed continued improvement in functional outcome in the elderly up to 1-year following severe TBI using the Health Related Quality of Life Measure, an improvement that was not appreciated using the GOSE (23). In addition, the GOSE does not distinguish disability related to neurological impairment from that of systemic injury or illness; one could then postulate that in the setting of increased co-morbidities in the elderly, GOSE scores remain low in the elderly secondary to non-neurological conditions.…”
Section: Discussionmentioning
confidence: 98%
“…While the GOSE is the most widely used measure of global functional outcome following TBI and has been recommended as the standard outcome measure for TBI studies, it has not been validated in the elderly population. One group showed continued improvement in functional outcome in the elderly up to 1-year following severe TBI using the Health Related Quality of Life Measure, an improvement that was not appreciated using the GOSE (23). In addition, the GOSE does not distinguish disability related to neurological impairment from that of systemic injury or illness; one could then postulate that in the setting of increased co-morbidities in the elderly, GOSE scores remain low in the elderly secondary to non-neurological conditions.…”
Section: Discussionmentioning
confidence: 98%
“…For example, a multi-center, prospective study of older adults with severe TBI found that although these patients experienced significant improvement in physical function over 1 year according to the Health Related Quality of Life Measure, this functional improvement was not detected by the GOSE. 160 Additionally, many in the field rely upon the 1998 GOS and GOSE administration and scoring guide by Wilson and colleagues. 161 Yet, even in this comprehensive guide, scoring of patients with preinjury disability is described as ''problematic.''…”
Section: Outcome Assessmentmentioning
confidence: 99%
“…GCS: Glasgow Coma Scale, ED: Emergency Department; HAIS: Head Abbreviated Injury Score; GOSE: Glasgow Outcome Scale extended; SF-12: General assessment instrument of health-related of quality of life. * Reference [30]. …”
Section: Tablementioning
confidence: 99%